2005
DOI: 10.1002/adsc.200404256
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Enantioselective Hydrogenation of Terminal Alkenes

Abstract: Iridium complexes derived from chiral P,N ligands are efficient catalysts for the enantioselective hydrogenation of 2-aryl-substituted terminal alkenes. Using 0.1 -1 mol % of catalyst at room temperature and ambient hydrogen pressure, high enantioselectivities (88 -94% ee), full conversions after short reaction times and essentially quantitative yields were obtained for a range of differently substituted 2-arylalkenes. Among six iridium complexes that were tested, the most selective catalyst was a complex with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…Since previous work on substrate 24 showed that low hydrogen pressure increases the asymmetric induction, [5,32] catalyst screening was performed at 1 bar H 2 gas pressure (Table 5).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Since previous work on substrate 24 showed that low hydrogen pressure increases the asymmetric induction, [5,32] catalyst screening was performed at 1 bar H 2 gas pressure (Table 5).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…132 For terminal allylic alcohols, the Ir-catalyzed asymmetric hydrogenation has achieved ee's up to 88% in the hydrogenation of S126 using phosphinite-oxazoline 19a (Figure 4) ligand (Table 7, entry 32). 67 Introducing a phosphite moiety in the ligand design is advantageous, achieving enantioselectivities up to 95% in the reduction of S127 (Table 7, entry 33).…”
Section: Allylic and Homoallylic Alcohols And Ethersmentioning
confidence: 99%
“…The complexes were characterized by elemental analysis and 1 H, 13 C, and 31 P NMR spectroscopy. The spectral assignments (see the Experimental Section) were based on information from …”
Section: Resultsmentioning
confidence: 99%
“…Few known catalytic systems provide high enantioselectivities for these substrates, and those that do are usually limited in substrate scope. [13,14] Pfaltz found that in the hydrogenation of terminal alkenes, the selectivity is highly pressure dependent. Hydrogenation at an atmospheric pressure of H 2 gave significantly higher ee values than at higher pressures.…”
Section: Entrymentioning
confidence: 99%
See 1 more Smart Citation